COST EVALUATION OF STROKE THERAPY COMPARED TO INA-CBGs ON INPATIENTS AT ANUTAPURA HOSPITAL - Muhamad Rinaldhi Tandah; Alwiyah Mukaddas; Dewi Angriani; Gaby Nathania Angela Mangoting (Universitas Airlangga, 2021)
ABSTRACTStroke is the third cause of death in the world after heart disease, cancer, and disability including disability categorized based on its severity: mild (I), moderate (II), and severe (III) severity. This study aims to determine the difference total cost of ischemic and hemorrhagic stroke therapy, each, with INA-CBGs rates. The method of data collection was conducted retrospectively taken from medical record data, and on patient medical expenses. The subject were ischemic and hemorrhagic stroke patients hospitalized from 2016-2017 at Anutapura Hospital who met the inclusion and exclusion criteria. There were 134 patients who met the inclusion criteria, 68% were ischemic stroke patients and 32% were hemorrhagic stroke patients. The result of research showed that there were significant differences in costs (p <0.05) between hospital real costs and INA-CBGs rates. The average total real cost of treatment for ischemic stroke therapy was IDR 7,360,196.70 and the cost of the INA-CBGs was IDR 7,427,251.65 for 91 inpatients; and the average total cost of patients with hemorrhagic stroke therapy took IDR 10,606,834.34 with average of INA CBG’s rate at IDR 4,399,393.02 for 43 inpatients. The conclusion is both of stroke therapy proved significant difference compared to BPJS claimed amount of money.Keywords: pharmacoeconomic, cost analysis, ischemic stroke, haemorrhage stroke, INA-CBG’s rate.